Perbandingan Pengetahuan dan Sikap tentang Imunisasi Vaksin HPV pada Remaja Putri Kelas X MAN dengan Remaja Putri Kelas X SMA N 5 Kota Batam: Comparison of Knowledge and Attitude about HPV Vaccine Immunization in Adolescents Woman of X MAN Class with Adolescents Woman of X Class SMA N 5 City Batam - Mastikana, Indah (Jurnal Surya Medika (JSM), 2021)
Prevention of dysplasia or pre-cancer is prevention before the arrival of cervical cancer is by Vaccine Immunization. The cervical cancer prevention program using HPV vaccination should have been obtained and known to young women in the educational process both at school and campus as well as through print and electronic media. The research design is descriptive-analytic with a cross-sectional approach. The sampling technique used nonprobability techniques with a sample size of 86 adolescents from each of the two schools. The result showed that of the 86 girls in SMA N 5 Batam City who had good knowledge, were 56 students (65.1%), only 26 students (30.2%) and less 4 students (4.7%) and that out of 86 girls in class X SMA N 5 Batam, as many as 78 students had positive attitudes (90.7%) and 8 student negative (9.3%) while the result of research at MAN Batam showed that from 86 girls who had good knowledge of 42 students (48.8%), quite 38 students (44.2%) and less than 6 students (7.0%) and of the 86 teenage girls of class X MAN Batam, 48 students had a positive attitude (55.8%) and 38 students (44.2%) negative attitude toward HPV Vaccine Immunization. The conclusion from the research results is that there is a majority of knowledge of adolescents SMAN 5 and MAN Batam have good knowledge and positive attitudes and there are significant differences in knowledge and there are no significant differences in attitude about HPV vaccine immunization.